Influence of Exogenous 24-Epicasterone on the Hormonal Status of Soybean Plants - Derevyanchuk, Michael; Kretynin, Serhii; Bukhonska, Yaroslava; Pokotylo, Igor; Khripach, Vladimir; Ruelland, Eric; Filepova, Roberta; Dobrev, Petre I; Martinec, Jan; Kravets, Volodymyr (Plants (Basel, Switzerland), 2023)
Brassinosteroids (BRs) are key phytohormones involved in the regulation of major processes of cell metabolism that guide plant growth. In the past decades, new evidence has made it clear that BRs also play a key role in the orchestration of plant responses to many abiotic and biotic stresses. In the present work, we analyzed the impact of foliar treatment with 24-epicastasterone (ECS) on the endogenous content of major phytohormones (auxins, salicylic acid, jasmonic acid, and abscisic acid) and their intermediates in soybean leaves 7 days following the treatment. Changes in the endogenous content of phytohormones have been identified and quantified by LC/MS. The obtained results point to a clear role of ECS in the upregulation of auxin content (indole-3-acetic acid, IAA) and downregulation of salicylic, jasmonic, and abscisic acid levels. These data confirm that under optimal conditions, ECS in tested concentrations of 0.25 µM and 1 µM might promote growth in soybeans by inducing auxin contents. Benzoic acid (a precursor of salicylic acid (SA)), but not SA itself, has also been highly accumulated under ECS treatment, which indicates an activation of the adaptation strategies of cell metabolism to possible environmental challenges.
Keywords: salicylic acid; hormones; 24-epicastasterone; auxins; soybean